Archbishop Agapit (Vishnevsky) against the backdrop of church, social and political transformations (1867-1923?). - Savchenko, Serhii (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2025)
Research Objective – to reconstruct the key stages of the biography of Archbishop Agapit (Vishnevsky) of Katerynoslav and Mariupol and to analyze his multifaceted activities within the context of the socio-political transformations of the early 20th century. The author examines the hierarch’s fate as a vivid reflection of the dramatic path of the Orthodox Church during the era of revolution and war, when the clergy found themselves compelled to adapt to fundamentally new conditions. Research Methodology encompasses historical-biographical and contextual approaches utilizing microhistorical principles. The source base includes publications from ecclesiastical periodicals, archival testimonies, materials from diocesan assemblies, and contemporary historiography. Particular attention is devoted to analyzing the archbishop’s administrative and public activities, his interactions with the clergy, public organizations, and authorities of various political regimes. Scholarly Novelty of the article lies in the comprehensive examination of Agapit’s ministry before and after the 1917 Revolution, including understudied episodes of his conflict with diocesan clergy, assessment of his response to political challenges, and reappraisal of his role in the ecclesiastical and social life of the Katerynoslav region. The article systematizes Agapit’s participation in the church politics of different regimes; for the first time, specific narrative and administrative documents are introduced into scholarly circulation, illuminating a number of little-known episodes (for example, the role of Archpriest Krechetovich, intra-diocesan conflicts, interaction with the Union of Russian People, perception of the hierarch in Katerynoslav); it is demonstrated that Agapit does not fit into the binary model of «Black Hundredist/autocephalist,» but rather occupies a complex, flexible position that emerged as a strategy of adaptation to the changing circumstances of revolutionary reality. Conclusions. Archbishop Agapit manifested himself as a pragmatic administrator who sought to preserve the stability of ecclesiastical life under conditions of changing political regimes. He maintained a balanced position between imperial loyalty and Ukrainian national tendencies; during the revolutionary period, he supported Ukrainization, participated episodically in the autocephalous movement, but subsequently distanced himself from this vector under the influence of circumstances. Under pressure from Soviet authorities, he joined the Renovationist movement. He attempted to find a canonically acceptable boundary of loyalty to changing political regimes in order to ensure peaceful ministry for his diocese and himself, but this tactic proved unsuccessful under conditions of Bolshevik anti-religious terror.